Maternal phenotype: how do age, obesity and diabetes affect myometrial function?. Issue 13 (February 2020) - Prendergast, Clodagh
Abstract : The prevalence of obesity and diabetes has increased rapidly in the general population over the last few decades, meaning that a significant number of women of reproductive age are now classified as obese and/or suffering from diabetes. More and more women are also delaying childbearing until older ages. This shift in maternal phenotype is accompanied by an increase in adverse pregnancy and labour outcomes. This review will summarise our current understanding of how maternal age, obesity and diabetes affect myometrial contractility and how these changes impact clinical outcomes.